Reproductive Biology of the Tenualosa ilisha in Labuhanbatu Regency, Sumatra Utara Province - Sam Syahra Jihad; Deni Efizon; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted from Juni to November 2013 in The Barumun River and in the laboratory of the Fishery Biology, Fisheries and Marine Sciences Faculty, Riau University. It aims to determine the reproductive biology of the tenualosa ilisha. Sex ratio, gonad maturating level, gonado somatic index, eggs diameter, fecundity were observed visually and analyzed based on Cassei (in Effendie, 1979). While histological characteristics of the gonad was studied based on Effendie (1979).111 fishes were caught and results indicated that male and female ratio was 3,2 : 1 and it was not significantly different (X2 test). The age of maturity of males was achieved by 120 g (BW) and 160 mm (SL), while that of the female was 400 g (BW) and 270 mm (SL). The body weight may increase as the gonad maturation level increase. The range of gonado somatic index was 0,3–25,0 %. The range of eggs diameter in the 4th maturity stage was 0,2–0,9 mm in diameter. The fecundity of (number of eggs) fish with 285–495 mm (SL) and gonad weight was around 81.450–245.267 eggs. Results of histological study shown that the eggs and sperm in the gonad are on several maturity stages.Keyword : Tenualosa ilisha, Barumun river, Sex ratio, Gonadal Maturating Index, Fecundity